Ocean Convection and Deep Water Circulation - Backhaus, Jan O.; Quadfasel, Detlef; Hainbucher, Dagmar (IWF (Göttingen), 1995)
The global oceanic thermohaline circulation (conveyor belt circulation) is driven at high latitudes through convection, the sinking of dense waters to great depths. The link between the convection itself and the large-scale circulation follows a cascade of processes on different spatial and temporal scales. Convection is intermittent and the sinking plumes are only a few hundred metres wide and have a life time of a few hours. The combined action of many plumes form, under the influence of the earth's rotation, meso-scale eddies of several kilometres width. Many of these again form the pool of newly formed water that subsequently spreads in the world oceans. The video explains this chain of scales leading from convection to the global ocean circulation, using results from numerical simulations and from observations made during a cruise of RV Valdivia in the Greenland Sea in winter 1994.